Ageing in Place in Urban Environments Critical Perspectives - Buffel, Tine (Aging and Society, 2024)
Ageing in Place in Urban Environments considers together two major trends influencing economic and social life: population ageing on the one side and urbanisation on the other. Both have been identified as dominant demographic trends of the twenty-first century. Cities are where the majority of people of all ages now live and where they will spend their old age. Nevertheless, cities are typically imagined and structured with a younger, working-age population in mind while older people are rarely incorporated into the mainstream of thinking and planning around urban environments. Cities can contribute to vulnerability arising from high levels of population turnover, environmental problems, gentrification, and reduced availability of affordable housing. However, they can also provide innovative forms of support and services essential to promoting the quality of life of older people. Policies in Europe have emphasised the role of the local environment in promoting "ageing in place", a term used to describe the goal of helping people to remain in their own homes and communities for as long as they wish. However, while this has been the dominant approach, the places in which older people are ageing have often proved to be challenging environments. The book explores the forces behind these developments and how older people have responded. Drawing upon approaches from social gerontology, urban studies, geography, and sociology, this book will be essential reading for researchers, policymakers, and practitioners searching for innovative ways to improve the lives of older people living in urban environments.